Where the wild things are - Sendak, Maurice ([New York] : Harper, 1988)
Max sails to the land of the wild things, where he becomes their king.
"Reprinted from new engravings made from the original art."
Adult 740
Accelerated Reader AR
Reading rainbow book
Caldecott Medal, 1964
Keywords: Monsters -- Juvenile fiction; Fantasy fiction